2013
DOI: 10.1021/es304606u
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Hexavalent Chromium Reducing Cathodes in the Presence ofShewanella oneidensisMR-1 and Lactate

Abstract: Biocathodes for the reduction of the highly toxic hexavalent chromium (Cr(VI)) were investigated using Shewanella oneidensis MR-1 (MR-1) as a bio-catalyst and performance was assessed in terms of current production and Cr(VI) reduction. Potentiostatically controlled experiments (-500 mV vs. Ag/AgCl) showed that a mediatorless MR-1 biocathode started up 2 under aerated conditions in the presence of lactate, received 5.5 and 1.7 times more electrons for Cr(VI) reduction over a 4-hour operating period than contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 34 publications
3
82
1
3
Order By: Relevance
“…However, as demonstrated elsewhere, this was not the case when oxygen was supplied in the MR-1-inoculated anode (Rosenbaum et al 2010;Xafenias et al 2013). In addition, this would not explain the slow recovery (or the absence of any recovery) observed after Cr(VI) depletion.…”
Section: Cr(vi) Reduction At Different Ph Valuesmentioning
confidence: 77%
See 3 more Smart Citations
“…However, as demonstrated elsewhere, this was not the case when oxygen was supplied in the MR-1-inoculated anode (Rosenbaum et al 2010;Xafenias et al 2013). In addition, this would not explain the slow recovery (or the absence of any recovery) observed after Cr(VI) depletion.…”
Section: Cr(vi) Reduction At Different Ph Valuesmentioning
confidence: 77%
“…In a previous study (Xafenias et al 2013), we demonstrated that lactate can act as a Cr(III)-chelating agent, enhancing the performance of neutral pH cathodes. However, neutral pH will rarely be the case of Cr(VI)-contaminated environments, and therefore, the effectiveness of this approach has to be tested at different pH ranges.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, since the Cr(VI) species (Cr 2 O 7 2-or CrO 4 2-) are electronegative and mutually exclusive against the negatively charged cathodes, the reduction of Cr(VI) and the electrochemical reaction kinetics are usually slow. The development of biocathodes based on the electrotrophic mediation between cathode electrode and Cr(VI) [12][13][15][16][17][18][19] appears to be a promising method for the reduction of Cr(VI) in…”
Section: Introductionmentioning
confidence: 99%